Vaping‐associated lung injury caused by inhalation of cannabis oil. Issue 1 (20th November 2019) - Abeles, Michael; Popofsky, Stephanie; Wen, Andy; Valsamis, Christina; Webb, Angela; Halaby, Claudia; Pirzada, Melodi
Abstract: Vaping is a growing concern in adolescents, and a growing proportion is using electronic devices to inhale cannabis oil. The short‐term and long‐term effects of cannabis oil inhalation are not well understood. We report on a case of severe acute lung injury secondary to inhalation of cannabis oil via a vape pen, and propose a new term that describes lung injury related to vaping.